Indoleamine 2,3-Dioxygenase 2 Immunohistochemical Expression in Resected Human Non-small Cell Lung Cancer: A Potential New Prognostic Tool - Mandarano, Martina; Bellezza, Guido; Belladonna, Maria Laura; Vannucci, Jacopo; Gili, Alessio; Ferri, Ivana; Lupi, Chiara; Ludovini, Vienna; Falabella, Giulia; Metro, Giulio; Mondanelli, Giada; Chiari, Rita; et al. (Frontiers in Immunology, 2020)
Indoleamine 2,3-dioxygenase 2 (IDO2) is an analog of the tryptophan degrading and immunomodulating enzyme indoleamine 2,3-dioxygenase 1 (IDO1). Although the role of IDO1 is largely understood, the function of IDO2 is not yet well-elucidated. IDO2 overexpression was documented in some human tumors, but the linkage between IDO2 expression and cancer progression is still unclear, in particular in non-small cell lung cancer (NSCLC). Immunohistochemical expression and cellular localization of IDO2 was evaluated on 191 formalin-fixed and paraffin-embedded resected NSCLC. Correlations between IDO2 expression, clinical-pathological data, tumor-infiltrating lymphocytes (TILs), immunosuppressive tumor molecules (IDO1 and programmed cell death ligand-1 – PD-L1 –) and patients' prognosis were evaluated. IDO2 high expression is strictly related to high PD-L1 level among squamous cell carcinomas group (p = 0.012), to either intratumoral or mixed localization of TILs (p < 0.001) and to adenocarcinoma histotype (p < 0.001). Furthermore, a significant correlation between IDO2 high expression and poor non-small cell lung cancer prognosis was detected (p = 0.011). The current study reaches interesting knowledge about IDO2 in non-small cell lung cancer. The close relationship between IDO2 expression, PD-L1 increased levels, TILs localization and NSCLC poor prognosis, assumed IDO2 as a potential prognostic biomarker to be exploited for optimizing innovative combined therapies with immune checkpoint inhibitors.